Influence of temperature on enhancement of volatile fatty acids fermentation from organic fraction of municipal solid waste: Synergism between food and paper components. (May 2020) - Soomro, Abdul F.; Abbasi, Irfan Ahmed; Ni, Zhe; Ying, Li; Liu, Jianguo
Graphical abstract: Highlights: Overall, synergism was observed across all temperature ranges (25–52 °C). PC can be used for VFA production at temperature of ≥42 °C. Optimized temperature for PWC, FWC and OFMSW were 52, 37 and 42 °C respectively. Mainly, acetic and butyric acids were produced from PC at 52 °C and FC at 37 °C. Abstract: This study explores individual contributions and synergistic effects of food and paper, main components of organic fraction of municipal solid waste (OFMSW) towards volatile fatty acids (VFA) fermentation under different temperatures (25, 37, 42 and 52 °C). Thanks to the synergism of food and paper component (FC & PC), the results revealed that OFMSW is suitable for VFA production. Maximum VFA production was noticed to be 21.5 mg/L at 42 °C, ~2.1, and 1.42 times higher than fermentation of PC and FC. Enhanced hydrolysis of PC occurred at >37 °C, increasing alkalinity in leachate to 6.7 g/L at 42 °C, thus maintaining a stable pH (5.4–5.6) during acidogenic fermentation. Additionally, 74% of COD is hydrolyzed, of which 79% is converted to VFA based on biodegradable carbon at 42 °C. It is suggested that co-existence of FC and PC can enhance VFA production of OFMSW, and targeted VFA production can be maximized through process optimization.